Microstructural evolution and performance of heat-treated Ti6Al4V in laser powder bed fusion - Farhana Mohd Foudzi,; Minhalina Ahmad Buhairi,; Fathin Iliana Jamhari,; Norhamidi Muhamad,; Intan Fadhlina Mohamed,; Abu Bakar Sulong,; Nashrah Hani Jamadon,; Nabilah Afiqah Mohd Radzuan, (Penerbit Universiti Kebangsaan Malaysia, 2025)
Ti6Al4V parts produced via laser powder bed fusion (LPBF) frequently exhibit high residual stress, where heat treatment has been utilized to relieve this stress. This study aims to investigate the effect of annealing heat treatment on the overall performance of Ti6Al4V fabricated using LPBF. Printed Ti6Al4V samples were heat treated at 935 °C for 8 h with a heating rate of 5 °C/min and a cooling rate of 0.60 °C/min. The overall performance such as physical properties, mechanical properties and microstructure observation between as-built and heat-treated samples were compared. The heat treatment was able to produce high-density parts, with surfaces as smooth as 5.70 μm, reaching up to 99.28% density. The annealing process significantly improved the ductility of Ti6Al4V parts by up to 231%, while decreasing the tensile strength by 28% and the hardness by 13%. The microstructure of as-built samples shifts from acicular α’ martensite to α+β phases after annealing at 935 °C for 8 hours, supporting the changes in mechanical performance. This preliminary study concludes that the heat treatment used following LPBF printing can create Ti6Al4V samples with acceptable physical, mechanical, and microstructure properties.